Quantitative Analysis of Indonesian Consumer Non-Cyclycal Sector: Fundamental Analysis on Stock Price - Hapsari, Ratih Regina; Nanda, Monica; Siahaan, Shintia Agnetha (MDP Student Conference, 2024)
This scientific article research aims to determine the influence of Return On Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Price to Equity Ratio (PER) on share prices in non-cyclical consumer sector companies used in This research is quantitative data. The data source used is secondary data in the form of annual financial reports. The research population is all technology sector companies listed on the Indonesia Stock Exchange for the period 2020 - 2022, namely 38 banking companies. The results of this research show that the Return On Equity (ROE) variable has a significant positive effect on stock prices, the Net Profit Margin (NPM) variable has a significant positive effect on stock prices, Debt to Equity Ratio (DER) has a positive effect on stock prices, and Price to Equity Ratio (PER) has a significant positive effect on share prices, companies in the technology sector listed on the Indonesian stock exchange for the 2020-2022 period